Evaluation in vitro of the antagonistic substances produced by Lactobacillus spp. isolated from chickens - Lima, Edna T. [UNESP] (2007)
To determine the inhibitory Qacity of lactic acid bacteria due to the action of antagonistic substances, we tested 474 isolates of Lactobacillus from the crop and cecum of chickens against gram-positive and gram-negative indicator microorganisms by the spot-on-the-lawn and well-diffusion antagonism methods. Of the 474 isolates, 265 demonstrated antimicrobial activity against the indicator microorganisms. Isolates identified as L. reuteri, L. salivarius, or Lactobacillus spp. inhibited Enterococcus faecalis, E. faecium, Listeria monocytogenes, and Salmonella spp. but not L. casei, L. delbrueckii, L. fermentum, or L. helveticus by the well-diffusion simultaneous antagonism method under anaerobic incubation conditions. The antagonistic substances produced by some of the Lactobacillus isolates were inactivated after treatment by proteolytic enzymes, which suggested that the substances could be antimicrobial peptides or bacteriocins.